Technology for teachers : mastering new media and portfolio development - Joseph H. Howell (Mc Graw-Hill Higher Education, 2000)
File dalam bentuk PDF, Gambar, Htm (internet), dll; Isi: ASSESS, Author, Evalute, Exercise, Internet, Learning, Manage, Present, Win 95, dll; Judul dalam kemasan.